E-050 Navigation of a Distal Cerebral Embolic Protection Device through Significant Vascular Tortuosity with a Novel Rapid Exchange Catheter System during Carotid Artery Stenting. (26th July 2014) - Ding, D; Starke, R; Evans, A
Abstract : Introduction: Carotid stenosis is a prevalent cause of ischemic cerebrovascular disease. Carotid endarterectomy and carotid artery stenting (CAS) have both been shown to provide effective and durable reductions in the risk of neurological morbidity and mortality for patients with carotid stenosis. Cerebral embolic protection devices (EPD) reduce the rate of periprocedural thromboembolic complications and are currently used in all CAS procedures. However, tortuous vascular anatomy of the internal carotid artery (ICA) may prevent navigation of distal EPDs thereby leading to inadequate cerebral protection. Methods: We present a case in which significant tortuosity of the ICA distal to the stenotic lesion precluded navigation of currently available distal EPDs. Results: An 80 year-old female presented with severe, symptomatic right-sided carotid stenosis. The patient elected to undergo CAS. A 6 French Envoy catheter was navigated into the right common carotid artery (CCA). Diagnostic angiography of the right CCA demonstrated 73% stenosis of the proximal ICA, 3 mm in length, with a severe inferior bend in the ICA just distal to the cervical segment. A Transend microguidewire was placed through an Angioguard distal protection device to bypass the stenotic lesion in the ICA. However, the Angioguard device could not be navigated past the tortuous bend in the ICA. A second attempt to pass through the tortuous ICA segment with a Spider distal protection device was also unsuccessful. The navigation of both EPDs past the tortuous ICA bend was prohibited due to kinking of their delivery catheters. In order to overcome the limitations imposed by the vascular tortuosity of the distal cervical ICA, a novel rapid exchange catheter system (RECS) was created to provide additional support for the EPD. A braided DAC 038 catheter was converted into a RECS by introducing two small bores with a 19-gauge needle. The Spider device and Transend guidewire were back-loaded into the DAC 038 catheter which was able to be navigated past the tortuous bend in the ICA. The Spider device could then be safely deployed in the cervical ICA allowing subsequent completion of the stenting procedure. Following deployment of the Spider device, a 4 × 20 mm TREK coronary balloon was used to angioplasty the ICA at the level of the stenosis prior to deploying an 8 × 30 mm Precise stent across the lesion. Post-stent angiography performed through the Envoy catheter in the right CCA showed significant improvement in the diameter of the proximal ICA lumen with an appropriately positioned stent spanning from the distal CCA to the proximal cervical ICA. Postprocedural carotid Doppler ultrasonography demonstrated minimal to mild residual stenosis of the right ICA measuring 0–39% with appropriate stent patency. The patient's postprocedural course was uneventful, and she remained neurologically intact at follow-up one month after CAS. Conclusions: We demonstrate that modification of currently available devices can, in select cases, effectively address cases of significant vascular tortuosity which limit the use of conventional distal EPDs. Disclosures: D. Ding: None. R. Starke: None. A. Evans: None.